Adsorption-attraction electrolyte addressing anion-deficient interface for lithium metal batteries - Pengbin Lai; Yaqi Zhang; Junhao Wang; Minghui Chen; Xinyu Li; Xiaodie Deng; Qichen Chen; Boyang Huang; Chaolun Gan; Yeguo Zou; Yu Qiao; Peng Zhang; et al. (eScience)
Constructing an optimal solid–electrolyte interphase (SEI) through electrolyte strategies is an effective approach to suppress lithium dendrites and improve deposition/stripping reversibility. Specifically, increasing the proportion of anion coordination in the inner Li+ solvation sheath promotes the formation of an anion-derived SEI that features a high content of inorganic components favoring Li+ diffusion. However, whether this anion-rich structure can persist during cycling has not been dynamically investigated. In this work, we not only construct a favorable solvation structure but also study its evolution in both bulk and interface regions across varying temperatures. Additionally, we employ the unique “adsorption-attraction” mechanism of trifluoromethoxybenzene (PhOCF3) solvent to inhibit the undesirable transition from an “anion-rich” to “anion-deficient” structure at the anode interface, which is confirmed by 2D NMR and in situ infrared spectroscopy. In summary, this work explores the solvation structure in depth and proposes new perspectives on designing electrolytes for lithium metal batteries.